The determinants of CDS open interest dynamics - Silva, Paulo (2016)
It has been argued that the CDS market may be a threat to financial stability. Such concern may stem from the counterparty risk assumed by market participants and the high sensitivity of these instruments to the business cycle. The open interest of the CDS market mirrors investors’ maximum exposure and captures aggregate inventory risk, liquidity risk, and trading activity. In this paper, we aim to identify the main determinants of the dynamics of two alternative measures of open interest, the gross and net notional amounts. Our results suggest that both asymmetry of information and divergence of opinions on firms’ future performance help explain the growth of the net notional amount of single-reference contracts, but systematic factors have a much greater influence. Net notional amount growth of different obligors co-varies in time and the dynamics of open interest is pro-cyclical. The CDS market expands following a positive stock market performance and contracts when large negative (positive) jumps in stock (CDS) prices are perceived by investors. In line with the market microstructure theory, funding costs and counterparty risk reduce CDS market players’ willingness to incur inventory risk, thus contracting gross notional amounts.